Exploring the therapeutic potential of “Tianyu” medicine pair in rheumatoid arthritis: an integrated study combining LC-MS/MS, bioinformatics, network pharmacology, and experimental validation - Tang, Lu; Guo, Dingyuan; Jia, Dongye; Piao, Songlan; Fang, Chunqiu; Zhu, Yueya; Wang, Yinghang; Pan, Zhi (Frontiers in Medicine, 2024)
Background: Rheumatoid arthritis (RA) is a widespread chronic autoimmune disease that primarily causes joint inflammation and damage. In advanced stages, RA can result in joint deformities and loss of function, severely impacting patients' quality of life. The 'Tianyu' pair (TYP) is a traditional Chinese medicine formulation developed from clinical experience and has shown some effectiveness in treating RA. However, its role in the complex biological mechanisms underlying RA remains unclear and warrants further investigation.We obtained gene sequencing data of synovial tissues from both RA patients and healthy individuals using two gene microarrays, GSE77298 and GSE55235, from the GEO database. Through an integrated approach involving bioinformatics, machine learning, and network pharmacology, we identified the core molecular targets of the "Tianyu" medicine pair (TYP) for RA treatment. Liquid chromatography-mass spectrometry was then employed to analyze the chemical components of TYP. To validate our findings, we conducted animal experiments with Wistar rats, comparing histopathological and key gene expression changes before and after TYP treatment.Results: Results: Our data analysis suggests that the onset of RA may be associated with inflammation-related immune cells involved in both adaptive and innate immune responses. Potential key targets for TYP treatment in RA include AKR1B10, MMP13, FABP4, NCF1, SPP1, COL1A1, and RASGRP1. Among the components of TYP, Kaempferol, Quercetin, and Salidroside were identified as key, with MMP13 and NCF1 showing the strongest binding affinity to these compounds. Animal experiments confirmed the findings from bioinformatics and network pharmacology, validating the key targets and therapeutic effects of TYP in treating RA. Conclusion: Our study reveals that TYP has potential clinical value in the treatment of rheumatoid arthritis. This research enhances our understanding of RA's pathogenesis and provides insight into potential therapeutic mechanisms.